Adaptation and validation of the Family Influence Scale in a sample of students from Serbia - Tasković, Milica; Ivana, (Psihološka istraživanja, 2024)
The main goal of this study was to evaluate the functional equivalence of the adapted version of the Family Influence Scale in measuring the influence of the family on career choices and development on a sample of  Serbian undergraduate and master's students. The sample consisted of 204 students (Mage= 22.24, SDage= 2.40, Minage =  18, Maxage = 34) of which 77.5% were females. To evaluate the construct validity of the adapted scale, principal components analysis, parallel analysis, and confirmatory factor analysis were emplyed. The obtained results indicate that there is an equal number of dimensions in both the original and adapted versions of the scale (Informational Support, Financial Support, Family Expectations and Values/Beliefs). Additionally, the convergent validity of the adapted scale was supported through correlations with the Support, Interference and Lack of engagement Scale. The nomological network of the adapted version was examined and mostly supported its equivalence with the original version. The internal validity of the scale was mostly supported by the interrelationships of its measures. Reliability analysis showed satisfying internal consistency. Specifically, the Cronbach's alpha values ranged from .650 to .837, and the McDonald’ ω values ranged from .669 to .838. Despite the limitations of the study, the adapted scale can be used to examine the possible family's influence on career choices and development among students in this cultural area (Bosnian-Croatian-Montenegrin-Serbian speaking area). This study provides valuable insights into the development of career-related measures that can be used in other cultural contexts as well.
Keywords: family influence, occupational choice, career development, adaptation, validation